Methods of phylogenetic inference - Peña, Carlos (2011)
There are three methods commonly used in phylogenetic studies of systematic: i) Cladistics, using the principle of maximum parsimony (MP), ii) Maximum Likelihood (ML) and iii) Bayesian inference (BI). In recent years there has often using Neighbor-Joining method (NJ), which is not a phylogenetic approach; in the following lines I will explain briefly why it should not be used to infer phylogenetic relationships.